TDARNAJOU TDARNAJOU Mathématiques Answered Développer et réduire les expressions suivantes : A = 3(x - 2) B = 5x(2x + 3) C = (x - 1)(x + 5) D = (2x - 1) (3x + 5) E = (x-7)² F = (3x + 2)² G = (5x - 3)² H = (x-4) (x + 4) I = (5x - 1) (5x + 1) J = (4x + 3) (4x - 3) Développer et réduire les expressions suivantes : A = 3(x - 2) B = 5x(2x + 3) C = (x - 1)(x + 5) D = (2x - 1) (3x + 5) E = (x-7)² F = (3x + 2)² G = (5x - 3)² H = (x4) (x + 4) I = (5x - 1) (5x + 1) J = (4x + 3) (4x − 3) Développer et réduire les expressions suivantes : A = 3(x - 2) B = 5x (2x + 3) C = (x - 1)(x + 5) D = (2x - 1)(3x + 5) E = (x-7)² F = (3x + 2)² G = (5x - 3)² H = (x-4) (x + 4) I= (5x - 1) (5x + 1) J = (4x + 3) (4x - 3) Développer et réduire les expressions suivantes : A = 3(x - 2) B = 5x(2x + 3) C = (x - 1)(x + 5) D = (2x - 1)(3x + 5) E = (x-7)² F = (3x + 2)² G = (5x - 3)² H = (x-4) (x + 4) I= (5x - 1) (5x + 1) J = (4x + 3) (4x − 3)